Health care waste management – 25 years on – what have we learned? - Krisiunas, Ed Peter (International Journal of Infection Control, 2014)
Health Care Waste (HCW) – just one of the numerous terms used to describe the wide range of waste streams emanating from any health care facility in the world. In fact, this waste can also be generated in non-traditional settings such as the home (diabetic self-injectors), tattoo and body piercing parlors, and pharmacies where some immunizations are administered. We are a society that generates waste streams that fall into many categories. We also know that how waste is managed around the world varies. HCW is no exception. Management of the infectious portion of the HCW stream has posed interesting challenges in the past 25 years. What are those challenges and what have we learned?